2006
DOI: 10.1191/0143624406bt142oa
|View full text |Cite
|
Sign up to set email alerts
|

A PCM/heat pipe cooling system for reducing air conditioning in buildings: review of options and report on field tests

Abstract: Air conditioning is now seen as a new and major contributor to CO2 emissions in the UK. This is partly due to global warming and partly to the increased use of IT systems. A novel system for reducing or eliminating the need for air conditioning was developed to the proof-of-concept stage under an earlier project at the University of Nottingham. The system makes use of heat pipes to transfer heat into and out of a phase change material which is ‘frozen’ during the night and ‘melted’ during the day. This paper d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The free cooling technique by using phase change materials in buildings can provide better indoor thermal comfort, and help reduce the need of air-conditioning use and sizes of air-conditioning systems (Turnpenny et al, 2000(Turnpenny et al, , 2001Zhu et al, 201;Etheridge et al, 2006). However, this concept is only feasible in climate conditions with relatively large temperature differences between day and night in Summer (Takeda et al, 2004;Medved and Arkar, 2008).…”
Section: Nomenclaturementioning
confidence: 96%
“…The free cooling technique by using phase change materials in buildings can provide better indoor thermal comfort, and help reduce the need of air-conditioning use and sizes of air-conditioning systems (Turnpenny et al, 2000(Turnpenny et al, , 2001Zhu et al, 201;Etheridge et al, 2006). However, this concept is only feasible in climate conditions with relatively large temperature differences between day and night in Summer (Takeda et al, 2004;Medved and Arkar, 2008).…”
Section: Nomenclaturementioning
confidence: 96%
“…They concluded that with the incorporation of HPHX the cooling capacity of the system is increased by 20% to 32.7% and the RH level maintained below 70%. Etheridge et al [2] have conducted a research on phase change material heat pipe cooling system for reducing AC in buildings. They report that the objective of their research is to retrofit the existing (AC) units in the buildings with previous cooling system on commercial scale and to reduce the carbon emission to save the environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Air has been used as HTF in specific occasions, such as in solar air heating systems, air preheaters, flue gas waste thermal recovery, and building heat . If water is used as HTF, then an air‐water heat exchanger should be added to transmit heat from water to air.…”
Section: Introductionmentioning
confidence: 99%